Adenovirus Type 37 Uses Sialic Acid as a Cellular Receptor on Chang C Cells - Arnberg, Niklas (American Society for Microbiology, 2002)
Epidemic keratoconjunctivitis (EKC) is a severe eye infection caused mainly by adenovirus type 8 (Ad8), Ad19, and Ad37. We have shown that the EKC-causing adenoviruses use sialic acid as a cellular receptor on A549 cells instead of the coxsackie-adenovirus receptor, which is used by most adenoviruses. Recently, Wu et al. (Virology 279:78-89, 2001) proposed that Ad37 uses a 50-kDa protein as a receptor on Chang C conjunctival cells and that this interaction is independent of sialic acid. According to the American Type Culture Collection, this cell line carries HeLa cell markers and should be considered to be a genital cell line. This prompted us to investigate the function of sialic acid as a cellular receptor for Ad37 in Chang C cells. In this study, we demonstrate that enzymatic removal or lectin-mediated blocking of cell surface sialic acid inhibits the binding of Ad37 virions to Chang C cells, as does soluble, virion-interacting sialic acid-containing substances. The binding was Ca(2+) or Mg(2+) ion independent and mediated by the knob domain of the trimeric viral fiber polypeptide. Moreover, Ad37 virions infected Chang C cells and two other genital cell lines (HeLa and SiHa) as well as a corneal cell line in a strictly sialic acid-dependent manner. From these results, we conclude that Ad37 uses sialic acid as a major receptor in cell lines derived from both genital and corneal tissues.